Efficacy of a 10% Magnesium Chloride Ointment for Seborrheic and Atopic Dermatitis: A Case Report - Sudan, Bernard J.L. (International Journal of Innovative Research in Medical Science, 2025)
After showing the potential involvement of magnesium chloride to stabilize tissue mast cells involved in the etiology of seborrheic dermatitis, the case of a patient with atopic hand dermatitis confirms the efficacy of a 10% magnesium chloride ointment. This observation is confirmed by a recent Japanese study showing the effectiveness of magnesium chloride and zinc chloride solutions in stabilizing rat peritoneal mast cells. Thus, in vitro research confirms the in vivo clinical observations. The local treatment of seborrheic and atopic dermatitis should therefore be redirected towards a more effective strategy without potential side effects, thus marking a great progress in dermatology.